2014
DOI: 10.1016/j.heares.2014.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Selective attention reduces physiological noise in the external ear canals of humans. I: Auditory attention

Abstract: In this study, a nonlinear version of the stimulus-frequency OAE (SFOAE), called the nSFOAE, was used to measure cochlear responses from human subjects while they simultaneously performed behavioral tasks requiring, or not requiring, selective auditory attention. Appended to each stimulus presentation, and included in the calculation of each nSFOAE response, was a 30-ms silent period that was used to estimate the level of the inherent physiological noise in the ear canals of our subjects during each behavioral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
61
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(70 citation statements)
references
References 70 publications
9
61
0
Order By: Relevance
“…The physiological measure used here was a nonlinear version of the stimulus-frequency otoacoustic emission (SFOAE), called the nSFOAE (Walsh et al, 2010a(Walsh et al, , 2014a. The SFOAE is a continuous tonal reflection that is evoked from the cochlea by a long-duration tone (Kemp, 1980); after a time delay, the reflection adds with the input sound in the ear canal.…”
Section: The Nsfoae Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…The physiological measure used here was a nonlinear version of the stimulus-frequency otoacoustic emission (SFOAE), called the nSFOAE (Walsh et al, 2010a(Walsh et al, , 2014a. The SFOAE is a continuous tonal reflection that is evoked from the cochlea by a long-duration tone (Kemp, 1980); after a time delay, the reflection adds with the input sound in the ear canal.…”
Section: The Nsfoae Proceduresmentioning
confidence: 99%
“…For each block of trials, the physiological responses from the trials having a correct behavioral response were based on about 20 to 30 trials. [Reprinted with permission from Walsh et al (2014a).] stimulus used to elicit the nSFOAE so that the presentation levels for the two earphones were as similar as possible.…”
Section: The Nsfoae Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…To efficiently extract the feature of the spectrogram, the selective attention mechanism is used. The selective attention mechanism is the high-level cognitive ability, which is helpful to pay attention to the target information and eliminate the interference [10]. The study on the auditory selective attention mechanism is very few and mainly focused on the research field of physiology and cognition [11].…”
Section: Spectrogram Feature Extractionmentioning
confidence: 99%
“…Activity in these muscles could affect thresholds by introducing acoustic noise or by impairing middle ear transmission. It has also been suggested that selective attention may reduce broadband noise associated with cochlear function via activation of the efferent system (Walsh et al 2014); in contrast to other sources of self-generated noise, cochlear noise is not predominantly low frequency.…”
Section: Introductionmentioning
confidence: 99%